Соціально-економічна нерівність населення крізь призму урбанізаційних процесів у Столичному макрорайоні України - Перегуда, Юлія; Pereguda, Julia (Східноєвропейський національний університет ім. Лесі Українки, 2017)
У сучасних умовах зростає необхідність висвітлення соціально-економічної нерівності населення з процесами урбанізації в межах Столичного макрорайону України. Мета статті − дослідження соціальноекономічної нерівності населення, а саме окреслення особливостей для формування середнього класу, які поєднуються з урбанізаційними процесами в межах Столичного макрорайону України. Досліджено та картографовано за показниками «щільність» і «чисельність» наявного населення в регіоні. За допомогою статистичних показників можливо наочно простежувати специфіку середнього класу та привести дані, які існують на певному етапі розвитку суспільства й у межах територіальних одиниць. Констатовано, що запровадження регіональної політики із врахуванням урбанізаційних процесів має включати всі складові елементи, що впливають на формування середнього класу. In modern conditions the necessity for coverage of socioeconomic inequality of population urbanization within Capital macrodistrict of Ukraine increases. The aim of the article is to study the socioeconomic inequality of the population, namely to define the features for a middle class that are combined with the help of urbanization processes within the Capital macrodistrict of Ukraine. Due to the indicators the density and population of the region have been studied and mapped. Due to the statistical indicators it is clearly possible to follow the specific class and provide data that exist at a certain stage of development of society and within the territorial units. Trends of increasingly uneven income and territories on which they live is a common problem of world economy, connected with the existing organization of market economy on a «center-periphery» principle. The development of the middle class should be considered in the formation of regional policy in the region and act as a key criterion for reform as a social and economic nature. The formation of the middle class deals with its importance in increasing living standards, reducing stratification within a certain territorial unit. It has been noted that with productive policies aimed at creating a framework for the development of the middle class, it will be possible to reduce the gap between rich and poor within the territory and provide an incentive for the development of infrastructure and economy in the territory based on the fundamentals for the formation of the middle class. It has been stated that the implementation of regional policy with regard to urbanization processes should include all the components that affect the formation of the middle class.
Socioeconomic Inequality in Terms of Population Urbanization Processes in Capital Macrodistrict of Ukraine
Keywords: середній клас; регіональний аналіз; соціально-економічна нерівність; регіональна політика; урбанізація; middle class; regional analysis; socioeconomic inequality; regional policy; urbanization